Perspectives for observing hot massive stars with XMM‐Newton in the years 2017–2027. Issue 2 (22nd March 2017) - Rauw, G.
Abstract : XMM‐Newton has deeply changed our picture of X‐ray emission of hot massive stars. High‐resolution X‐ray spectroscopy, as well as monitoring of these objects, has helped us to gain a deeper insight into the physics of single massive stars with or without magnetic fields, as well as of massive binary systems, where the stellar winds of both stars interact. These observations also revealed a number of previously unexpected features, challenging our understanding of the dynamics of the stellar winds of massive stars. Here, we briefly summarize the results obtained over the past 15 years and highlight the perspectives for the next decade. It is anticipated that coordinated (X‐ray and optical or ultraviolet) monitoring and time‐critical observations of either single or binary massive stars will become the most important topics in this field over the coming years. Synergies with existing or forthcoming X‐ray observatories (NuStar, Swift, and extended ROentgen Survey with an Imaging Telescope Array (eROSITA)) will also play a major role and will further enhance the importance of XMM‐Newton in our quest for understanding the physics of hot massive stars.